ANALISIS FAKTOR PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MINUMAN PADA BERINGIN COFFEE BATAM - Julisman,; Susi Marni,; Lutfi Erwin Lubis, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The purpose of this study was to analyze the factors influencing consumer behavior such as social, cultural, behavioral, and personal factors on the decision to purchase drinks at Café Beringin Batam. This sampling method uses saturated sampling with a total of 100 respondents. This type of research was quantitative, namely by distributing questionnaires to the Likert scale model which were analyzed using the classical assumption test and multiple linear regression with the SPSS statistical tool. The results of this study indicate that cultural and behavioral factors have a positive and significant influence on purchasing decisions at Café Beringin Coffee Bata. While personal and social factor variables do not affect. Besides that, the behavioral factor variable is the factor that most influences the purchasing decision